THE USAGE OF POLYSEMY IN DICTIONARIES AND CONTEXTS - Tukhtayeva Munisa Saidoqil kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
For lexical semanticists and lexicographers alike, polysemy—the phenomenon in which a language unit manifests numerous unique yet related meanings—has always been a subject of significant interest. The main purpose of this article is to determine how context affects how polysemous lexical elements are interpreted in their various senses.